2010
DOI: 10.1111/j.1748-7692.2010.00403.x
|View full text |Cite
|
Sign up to set email alerts
|

Replacement dolphins? Social restructuring of a resident pod of Atlantic bottlenose dolphins, Tursiops truncatus, after two major hurricanes

Abstract: Environmental variations can influence the structure of ecological communities that in turn alter the grouping and association patterns of social communities. This study compares the social structure of bottlenose dolphins in the Bahamas before and after two major hurricanes. Approximately 30% of regularly seen individuals disappeared after the hurricanes, with an equal number of immigrants arriving afterwards. The primary goal of this study was to quantitatively describe social structure changes occurring aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
73
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(78 citation statements)
references
References 48 publications
5
73
0
Order By: Relevance
“…Such a nested ranging behaviour among Guiana dolphins from different modules suggests that space use patterns are not enough to explain the modular topology observed in this study. However, nonsocial factors can still be influencing this dolphin social network (see Whitehead 1999;Parsons et al 2009;Elliser & Herzing 2011). We showed that the population dynamics has split this society into temporal modules.…”
Section: In the Same Placementioning
confidence: 82%
See 1 more Smart Citation
“…Such a nested ranging behaviour among Guiana dolphins from different modules suggests that space use patterns are not enough to explain the modular topology observed in this study. However, nonsocial factors can still be influencing this dolphin social network (see Whitehead 1999;Parsons et al 2009;Elliser & Herzing 2011). We showed that the population dynamics has split this society into temporal modules.…”
Section: In the Same Placementioning
confidence: 82%
“…Lehmann & Boesch 2004), which may define distinct social units (e.g. Elliser & Herzing 2011). The Guiana dolphin population underwent a marked population turnover, with a change in the population composition from the beginning to the end of the study.…”
Section: At Different Timesmentioning
confidence: 99%
“…Studies typically either examine the effects of anthropogenic disturbance from boats and tourism ( e.g., Nowacek et al 2001; Constantine et al 2004; Bejder et al 2006 a , b ; Dans et al 2008; Stockin et al 2008) or human‐generated noise in the marine environment ( e.g., Nowacek et al 2007, Weilgart 2007, Tyack 2008). However, a growing body of research is focusing on the effects of natural disturbance regimes such as HABs (Fire et al 2008 b , Goldstein et al 2008, Fire et al 2009, Torres de la Riva et al 2009), periodic environmental oscillations including El Niño (Wells et al 1990, Benson et al 2002, Lusseau et al 2004, Whitehead and Rendell 2004, Keiper et al 2005, Ballance et al 2006, Leaper et al 2006, Trathan et al 2007), and catastrophic events such as hurricanes (Miller et al 2010; Elliser and Herzing 2010) on marine mammal populations.…”
mentioning
confidence: 99%
“…In Little Bahama Bank, two hurricanes caused the loss of 30% of a population that comprised only one community (Elliser & Herzing, 2010). The remaining individuals formed two separate communities, each integrating immigrants.…”
Section: Discussionmentioning
confidence: 99%